2012
DOI: 10.1155/2012/973897
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Cytogenetics to the Debate on the Paraphyly ofPachycondylaspp. (Hymenoptera, Formicidae, Ponerinae)

Abstract: We present evidence of the paraphyly of the ant genusPachycondylaresulting from our cytogenetic studies on 29 populations in 18 species from Brazil and French Guyana. It is likely that karyotypes with a large number of chromosomes and comprising mostly small acrocentric chromosomes in species within thePachycondyla stricto sensugroup resulted from a succession of centric fission events. On the other hand, karyotypes with a small chromosome number comprising mostly metacentric chromosomes are also interpreted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 26 publications
3
38
0
1
Order By: Relevance
“…Mariano et al (2012) reported for the genus Pachycondyla a variation ranging from 2n = 12 [Pachycondyla unidentata Mayr 1862] to 2n = 104 [Pachycondyla striata (Smith 1858)]. These results strengthen the idea of paraphyly of the genus proposed by Schmidt (2013).…”
Section: Resuménsupporting
confidence: 68%
See 2 more Smart Citations
“…Mariano et al (2012) reported for the genus Pachycondyla a variation ranging from 2n = 12 [Pachycondyla unidentata Mayr 1862] to 2n = 104 [Pachycondyla striata (Smith 1858)]. These results strengthen the idea of paraphyly of the genus proposed by Schmidt (2013).…”
Section: Resuménsupporting
confidence: 68%
“…Such a pattern has been observed in other species of the same genus (Lucas et al 2002;Delabie et al 2008;Mariano et al 2012;Fernandes et al 2014) as in other genera such as Myrmecia (pilosula) (Imai et al 1994), all suggesting that a single morphospecies may correspond to 2 or more genetically isolated taxa . Additionally, morphological analyses of individuals of P. harpax collected in other locations, where cytogenetic analysis was not possible, revealed obvious differences, suggesting genetic divergence and possible karyotype variability.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Mariano et al (2008) interpreted the karyotype differences between populations as being due to a division of the species into allopatric populations during the Quaternary. Variability in the karyotype within a described species has been found in the Pachycondyla as well, and may represent cryp-tic species (Mariano et al 2012). Descriptions of the banding patterns on Dinoponera chromosomes are provided by Barros et al (2009) andde Aguiar et al (2011).…”
Section: Genus Dinoponera Roger 1861mentioning
confidence: 99%
“…The evolutionary position of the genus within Ponerinae was resolved by Schmidt (2010). Based on the phylogenetic analysis of Schmidt (2010) and karyotype analysis by Mariano et al (2012), Dinoponera's closest living relatives are in the Pachycondyla species group consisting of P. crassinoda, P. harpax (Fabricius 1804), P. impressa, P. metanotalis Luederwaldt 1918, andP. striata Smith 1858.…”
Section: Genus Dinoponera Roger 1861mentioning
confidence: 99%